Fósforo, potássio e cobre em neossolo sob cultivo centenário de videira - Korchagin, Jackson (2014)
Successive applications of copper fungicide, potassium and phosphate fertilizers in vineyards can cause the accumulation of copper, phosphorus and potassium in soil. The accumulationof theses ions in the soil favors the increase in soluble forms and enhances the transfer to the environment and contamination risk. The study aimed to assess the availability of copper, phosphorus and potassium in a Regosol under a vineyard, checking the possible migration of elements in the soil profile as well as the availability of ions in the vine rhizosphere. Two areas in the municipality of Pinto Bandeira in Rio Grande do Sul were studied: one under vineyard since 1890 and another under native forest (control). Soil samples at 0-50 cm depth were collected for physicochemical characterization. Soil samples were also collected in the rhizosphere of grapevine (RV) in the rows, 1,5 m apart from the vine plants (EL) and under native forest (MN). The ions availability were determined by the Mehlich -1 and cations and anions exchange resin (RTCA). The copper fungicide application increased the amount of Cu extracted by Mehlich-1 in the whole soil profile. The Cu concentration at 0-20 cm depth. was ~1,300 mg kg -1 The soil under the grapevine presented higher contents of phosphorus and less of potassium compared to native forest. The RV presented higher desorption potential for copper and phosphorus compared to EL and MN. However, the potassium contents were higher at MN when compared to the (RV and EL). The copper, phosphorus and potassium availability in soil under the vineyard after 123 years correspond to the amounts applied historically, the affinity of each ion to the soil particle, the losses , the agroecosystem exportation and the rizosphere influence.